Modified Buongiorno model for MHD micropolar and Casson hybrid nanofluid transportation with nonlinear thermal radiation through porous channel - Yahya, Asmat Ullah; Salamat, Nadeem; Abdal, Sohaib; Shah, Nehad Ali (Journal of thermal analysis and calorimetry, 2025)
A magnetohydrodynamic flow of hybrid-based (C 2 H 6 O 2 –H 2 O) micropolar fluid with homogenous mixture of two nanospecies (Fe 3 O 4 and MOS 2 ) is studied numerically. The non-Newtonian fluid dynamics is formulated as Casson flow model as well. The dynamical characteristics of heat and mass transfer are subject to be confined within a porous parallel plates channel in the existence of magnetic field and nonlinear radiation heat source. A set of apposite similarity type functions is employed to yield transmuted ordinary differential form of the primary partial differential formulation. Then, resulting ODEs are resolved by harnessing RK45 procedure with MATLAB script. The computations are carried out to evaluate the impacts of embedded factors on the dependent physical quantities mainly concentration of nanoentities, microrotation of fluid particles, hybrid fluid velocity and temperature. The magnetic parameter M significantly affects the velocity profile near the wall of the channel; due to perpendicular magnetic field lines velocity of fluid decreases. Increasing in Reynolds number Re and M leads to a decrease in microrotation velocity near the parallel walls of channel due to increase in Lorentz force. The temperature attains high values in case of hybrid nanofluids because of increased in concentration of nanoparticles. The addition of the nonlinear thermal radiation also increases the atomic vibratory motion of fluid particles, and this leads to enhance fluid temperature of the fluid near the walls of channel. Concentration of hybrid nanofluid increases due to enlarging thermophoresis parameter Nt and decreases due to increasing values of Brownian motion parameter Nb of nanoparticles.